2023
DOI: 10.1186/s12891-023-06946-1
|View full text |Cite
|
Sign up to set email alerts
|

Candy box technique for the fixation of inferior pole patellar fractures: finite element analysis and biomechanical experiments

Wei Fan,
Jinhui Liu,
Xiaoqi Tan
et al.

Abstract: Background Maintaining effective reduction and firm fixation in inferior pole patellar fractures is a highly challenging task. There are various treatment methods available; although tension-band wiring combined with cerclage wiring (TBWC) is the mainstream approach, its effectiveness is limited. Herein, we propose and evaluate a new technique called candy box (CB), based on separate vertical wiring (SVW), for the treatment of inferior pole patellar fractures. Specifically, we provide biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Then, the fixed wire around the periphery of the patella was replaced with two wires on the side of the patella through the bone tunnel ( Figure 1 ). Our team has previously confirmed both biomechanical advantages and potential clinical benefits associated with CB technology ( Fan et al, 2023 ).…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…Then, the fixed wire around the periphery of the patella was replaced with two wires on the side of the patella through the bone tunnel ( Figure 1 ). Our team has previously confirmed both biomechanical advantages and potential clinical benefits associated with CB technology ( Fan et al, 2023 ).…”
Section: Methodsmentioning
confidence: 62%
“…In this new approach, we replace the circumferential wire of the SVWC technique with two transverse bone tunnel wires positioned at the upper/middle 1/3 of the patella. We then conducted finite element analysis and biomechanical testing, which confirmed that the CB technique performs exceptionally well under different loads ( Fan et al, 2023 ). However, there is currently no definitive explanation for the optimal positions of vertical bone tunnel steel wires in SVW technology and horizontal bone tunnel steel wires in CB technology.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation